Causal associations of birth body size and adult body size with systemic lupus erythematosus: a bidirectional mendelian randomization study - Peng, Juan; Wang, Huizi; Li, Yanjuan; Dong, Xudong (Frontiers in Genetics, 2024)
Objective: Body size is associated with the onset of systemic lupus erythematosus (SLE). However, the evidence for this association is inconclusive. In this study, we aimed to investigate the causal relationship between body size and SLE. Method: We performed a bidirectional Mendelian randomization (MR) analysis that utilized summary statistics sourced from genome-wide association study (GWAS) data obtained from the IEU Open GWAS project website. The inverse variance weighting (IVW) method was used to evaluate the causality, and four additional MR methods were used to supplement the IVW results. Sensitivity analyses were performed using the Cochran's Q test, MR-Egger regression, leave-one-out analysis, and the Mendelian Randomization Pleiotropy RESidual Sum and Outlier (MR-PRESSO) global test. Results: In the forward direction analysis, the IVW model demonstrated that birth weight (odds ratio (OR), 1.811; 95% confidence interval (CI), 1.174-2.793; P<0.05) and adult height (OR, 1.225; 95% CI, 1.046-1.434; P<0.05) were positively associated with SLE. Four additional MR scans were performed parallel to the IVW results. Conversely, SLE was a weak causal factor for increased height (OR, 1.010; 95% CI, 1.002-1.018; P<0.05) using the IVW method. Heterogeneity, MR-Egger intercept, and leave-one-out analyses indicated that the results were robust. The MR-PRESSO suggested the presence of pleiotropy. Following the exclusion of instrumental variables (IVs) inducing pleiotropy, subsequent MR analysis yielded consistent results, thereby reinforcing the robustness of our findings. Conclusions: Positive causal associations were observed between birth weight, adult height, and SLE incidence. In the reverse analysis, SLE was a weak causal factor for adult height.